(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Surrogacy in a controversial issue with various edges, this document is based on the approach and description of altruistic and remunerated surrogacy management. Therefore, it leaves open the line of investigation in the law of the parties involved (contracting father, pregnant woman and the minor). Describes the States of the Mexican Republic that consider surrogacy, pointing out the scope and factors that intervene such as morality, religion, the political and legislative aspect based on the recognition and guarantee of human rights in gender matters, specifically of women and the best interests of the minor. Finally, based on an interpretive and analytical process, the notes of the surrogate management offer the reader a criterion and perspective of the scope of this process within the scope of law.